Isolated Primary Echinococcosis of Breast: A Rare Case Report - Liubota, Roman; Anikusko, Mykola; Zotov, Olexyy; Vereshchako, Roman; Liubota, Iryna (Archive of Oncology, 2017)
Isolated echinococcosis or hydatid cyst of breast is very rare disease especially in non-endemic areas. Even in endemic areas, hydatid cysts detects only for 0.27% of all cases of hydatidosis. Diagnosis of hydatid disease is difficult and its diagnosed after surgical excision in majority cases. We report a case of 39 year old female with isolated hydatid cyst of the left breast that was appeared as a painless breast lump without any specific symptoms.